MODERASI BERAGAMA SEBAGAI UPAYA PREVENTIF TERHADAP RADIKALISME BERAGAMA - Saepudin, Asep (Balai Diklat Keagamaan Bandung, 2023)
This article aims to describe that religious moderation is a preventive measure against religious radicalism. This research is a type of library study. The data collected in this research is qualitative data. The results of this research indicate that the city of Bandung needs a comprehensive concept of religious moderation to overcome the problem of religious radicalism through the concept of moderation. The threat of radicalism should not be considered normal, so it is very important to instill and demonstrate religious moderation to prevent the influence of radicalism. Tolerance is a concept that can reduce religious radicalism. The essence of the concept of tolerance is to provide space for other people to express their beliefs, convey their thoughts, voice their ideas and opinions even if they differ from other people opinions.